(untitled) (Research, Society and Development, 2020)
Ao longo da história, uma produção de plantas ornamentais tornou-se uma forma de agricultura altamente especializada e intensiva. O objetivo trabalho foi avaliar a utilização do caule decomposto do babaçu (CDB) na produção de dracena vermelha ( Cordyline terminalis)) seedlings by vegetative propagation. The experiment was conducted in a greenhouse with 70% luminosity control from October to December 2018, at the Center for Agricultural and Environmental Sciences at the Federal University of Maranhão.). Six substrate formulations: S0: 100% soil; S20: 20% CDB + 80% soil; S40: 40% CDB + 60% soil; S60: 60% CDB + 40% soil; S80: 80% CDB + 20% soil; S100: 100% CDB, were distributed in a completely randomized design with 4 replications, totaling 24 experimental units. Stake survival was evaluated (PS,%); the number of shoots (NB) and leaves (NF); leaf area (AF, cm²); diameter of the largest bud (DMB, cm); root length (CR, cm); root volume (VR, cm³); dry mass of aerial part (MSPA, g) and root (MSR, g) by ANOVA followed by comparison of means by the Tukey test at 5% significance. There was a significant effect for PS, MFSR and AF. The decomposed babassu stem can be used as a substrate for the vegetative propagation of red dracene, and a 60/40 CDB/soil ratio is recommended.